Innovative Instructional Design for Photography Education in Higher Education: A Multimedia and Project-Based Learning - Pradana, Hirnanda Dimas; Kristanto, Andi; Sumarno, Alim (Universitas Negeri Makassar, 2025)
Challenges facing higher education in photography remain the perennial difficulty of ensuring that the students deeply understand the technical and aesthetic concepts. Prior studies have found that many students still do not grasp the ideas of lighting techniques, composition, and camera operation. The problems directly affect the quality of their photographic products. An innovative learning medium that is highly visually attractive and can actively engage students in the learning process is required to rectify this situation. This study, therefore, designs an interactive multimedia-based instructional medium whose development is integrated with a Project-Based Learning (PjBL) approach to improve photography education at the higher education level. The model used for development is the Lee & Owens model, consisting of five stages: analysis, design, development, implementation, and evaluation. The choice of this model was based on its relevance to multimedia development, which highlights structured content and real-world outcomes. The developed media underwent validation by media experts and content experts and through individual checks in small groups and field testing. Results of the validation placed it at very good and feasible for use, affirming the proposition that integrating interactive multimedia and PjBL effectively supports photography learning, increases student engagement, and produces meaningful and contextual educational experiences.